A ring recovery of a lesser spotted Eagle Aquila Pomarina Brehm - H.P. Mendelsohn (Koedoe: African Protected Area Conservation and Science, 1975)
<!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } --> During ringing operations in the Punda Milia area of the Kruger National Park, Republic of South Africa, a Lesser Spotted Eagle, Aquila pomarina, Roberts Nr. 136, was caught by means of a bal-chatri trap at Magoane. The bird, an adult, had a mass of 1,26 kg, which appears light for its size; it was probably a male. It was fitted with a flanged ring of 16 mm diameter, No. 526-0727 at the time of capture - 29.11.1972, 08h00. A number ofconspecifics were observed in the area at the time. The eagle was recovered on 30.10.1973 and, as the ring was returned, it is presumed to be dead. The place of recovery was Azerbaijan SSR, near Kusary, U.S.S.R., co-ordinates 41 24'N, 48 27'E, which places it just north of the Caucasus Mountains and west of the Caspian Sea. It would appear that the eagle met its end shortly before or during migration, as the date of recovery given is only thirty days prior to the date on which the bird was ringed in the proceeding year.